Implementation of the Policy for Implementing Online Learning in the Era of the Covid-19 Pandemic at Army Officer Candidate Schools - Jamrizal, Jamrizal; Umanto, Umanto (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The Indonesian government has implemented various regulations to suppress the Covid-19 case. The majority of these policies limit mass activities, such as education. Thus, online education policies were initiated via various platforms with the need for access via the internet. However, military education institutions such as Secapa AD require face-to-face interactions and field-based learning to obtain appropriate learning outcomes. Therefore, a special policy was created for Diktukpassus T.A. 2021 which briefly has a quarantine period at the beginning of education. This period was filled with online learning. Various challenges, both external and internal, must arise. This research will reveal the opinions of students and teachers regarding the implementation of online learning using the interview and FGD methods. In the end, the respondents' sentiments led to the choice of studying offline rather than online. However, respondents also felt that online learning had a positive side and room for growth.